Discussion of “The Internet downturn: Finding valuation factors in Spring 2000” - Lewellen, Jonathan (Journal of Accounting and Economics, 2003)
This article reviews ‘The Internet downturn: Finding valuation factors in Spring 2000’ by Keating, Lys, and Magee (KLM). Their paper contributes to a growing literature on the valuation of Internet firms, finding strong relations among market prices, accounting variables, and assorted ‘new economy’ measures of performance. I argue that their results tell us more about investors’ (mis-)perceptions in Spring 2000 than about the underlying economics of Internet firms. Moreover, the valuations seem unlikely to repeat. KLM's findings may not generalize to other firms or time periods.